Women in Fiction: Beauty vs. Intelligence Daniel Defoe’s Moll Flanders (مجلة ديالى للبحوث الانسانية, 2022)
Beginning with the story of Adam and Eve in the Bible and throughout ensuing fiction, the role of women has been most prominent. William Dean Howells asserts, in his Heroines of Fiction (1901), that the greatness of any piece of fiction depends on the importance of its women, and that realistic fiction succeeded better than any former romance (p. 113) in this respect.    This paper’s purpose is to study a series of fascinating women who enlivened the fictional worlds in which they lived, beginning with Defoe’s Moll Flanders, showing the role of these women in their respective stories. It seems that male writers’ emphasis is more on physical beauty than intelligence while in female novelists’ writing the emphasis falls more on intelligence.